Health care providers' training, perceptions, and practices regarding stress and health outcomes. - Avey, Holly (National Medical Association, 2003)
In order to assess health care providers' training, perceptions, and practices regarding stress and health outcomes, a survey was administered to primary care providers in the outpatient medical clinics of a southeastern urban hospital serving a predominantly African-American indigent population. One-hundred-fifty-one of 210 providers (72%) responded. Forty-two percent of respondents reported receiving no instruction regarding stress and health outcomes during their medical/professional education. While 90% believed stress management was "very" or "somewhat" effective in improving health outcomes, 45% "rarely" or "never" discussed stress management with their patients. Respondents were twice as likely to believe that counseling patients about smoking, nutrition, or exercise was more important than counseling them about stress. Seventy-six percent lacked confidence in their ability to counsel patients about stress. The majority of respondents (57%) "rarely" or "never" practiced stress reduction techniques themselves. Belief in the importance of stress counseling, its effectiveness in improving health, and confidence in one's ability to teach relaxation techniques were all related to the probability that providers would counsel patients regarding stress. There is a need for curriculum reform that emphasizes new knowledge about stress and disease, new skills in stress reduction, and more positive beliefs about mind/body medicine and its integration into the existing health care structure.